2011
DOI: 10.4049/jimmunol.1003349
|View full text |Cite
|
Sign up to set email alerts
|

IFN-α Production by Plasmacytoid Dendritic Cells Stimulated with RNA-Containing Immune Complexes Is Promoted by NK Cells via MIP-1β and LFA-1

Abstract: Several systemic autoimmune diseases display a prominent IFN signature. This is caused by a continuous IFN-α production by plasmacytoid dendritic cells (pDCs), which are activated by immune complexes (ICs) containing nucleic acid. The IFN-α production by pDCs stimulated with RNA-containing IC (RNA-IC) consisting of anti-RNP autoantibodies and U1 small nuclear ribonucleoprotein particles was recently shown to be inhibited by monocytes, but enhanced by NK cells. The inhibitory effect of monocytes was mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 48 publications
5
74
1
1
Order By: Relevance
“…Mechanistically, NK cells promoted RNA-IC-induced IFN-a secretion by pDCs via soluble factors, such as MIP-1b, and via LFA-1-dependent cell-cell interactions. In addition to IFN-a, the secretion of several cytokines and chemokines implicated in the pathogenesis of SLE (e.g., IFN-g, IL-6, IL-8, MIP-1b, and TNF-a) was also enhanced in RNA-IC-stimulated pDC-NK cell cocultures (15). Consequently, pDC-NK cell cross-talk could be important in promoting sustained type I IFN production and the inflammatory response in systemic autoimmune diseases.…”
Section: S Ystemic Lupus Erythematosus (Sle) Is An Autoimmunementioning
confidence: 99%
See 4 more Smart Citations
“…Mechanistically, NK cells promoted RNA-IC-induced IFN-a secretion by pDCs via soluble factors, such as MIP-1b, and via LFA-1-dependent cell-cell interactions. In addition to IFN-a, the secretion of several cytokines and chemokines implicated in the pathogenesis of SLE (e.g., IFN-g, IL-6, IL-8, MIP-1b, and TNF-a) was also enhanced in RNA-IC-stimulated pDC-NK cell cocultures (15). Consequently, pDC-NK cell cross-talk could be important in promoting sustained type I IFN production and the inflammatory response in systemic autoimmune diseases.…”
Section: S Ystemic Lupus Erythematosus (Sle) Is An Autoimmunementioning
confidence: 99%
“…Previous studies showed that NK cells interact with pDCs to potently enhance IFN-a production upon stimulation with viruses, synthetic oligonucleotides, or RNA-containing ICs (RNA-ICs) (13)(14)(15). Mechanistically, NK cells promoted RNA-IC-induced IFN-a secretion by pDCs via soluble factors, such as MIP-1b, and via LFA-1-dependent cell-cell interactions.…”
Section: S Ystemic Lupus Erythematosus (Sle) Is An Autoimmunementioning
confidence: 99%
See 3 more Smart Citations